한국인 급성 심근경색증 등록 연구에서 성별에 따른 임상적 특징과 초기 치료의 차이 - 이기홍; 정명호; 안영근; 김종현; 채성철; 김영조; 허승호; 성인환; 홍택종; 최동훈; 조명찬; 김종진; et al. (Korean circulation journal, 2007)
배경 및 목적： 우리나라에서 최초로 인터넷을 이용한 급성 심근경색증 환 자의 등록(Korea Acute Myocardial Infarction Registry: KAMIR)이 2005년 11월부터 전국 41개의 일차적 관상동맥 중재술이 가능한 병원(primary PCI center)을 중심으로 시작 되었다. KAMIR에서 우리나라 급성 심근경색증 환자 치료에 있어 성별의 차이가 있는지 알아보고자 하였다. 방 법： 2005년 11월부터 2006년 6월까지 KAMIR에 등록된 환자 4,905명 중 완벽한 자료 분석이 가능한 4,110명(남성 2,855명, 여성 1,255명, 나이 64.3±13.5세)을 대상으로 하였다. ST 분 절 상승 심근경색증(ST-elevation myocardial infarction: STEMI)과 비-ST 분절 상승 심근경색증(non-ST elevation myocardial infarction: NSTEMI) 각각의 영역에서 성별에 따른 치료 방법의 차이를 분석하였다. 결 과： STEMI 초기 치료의 선택에 있어 남성이 여성보다 일차적 관상동맥 중재술(percutaneous coronary intervention: PCI) 을 많이 시술 받았으나(69.8% vs. 68.3%, 15.0%, p=0.008), 초기 치료의 선택에 있어 고려해야 하는 다른 인자들을 보정 한 후에는 유의한 차이를 보이지 않았다. 입원 기간 전체에 걸쳐 실시된 PCI는 STEMI, NSTEMI 모두 남성에서 여성보 다 많이 시행되었다(STEMI: 89.1% vs. 84.9%, p=0.004; NSTEMI: 74.7% vs. 63.5%, p<0.001). 삽입되는 스텐트 종 류는 STEMI에서 남성과 여성의 차이가 없었지만 NSTEMI 에서 남성이 여성보다 약물 용출 스텐트를 더 많이 시행받았 다(92.2% vs. 90.8%, p=0.022). PCI 성공률은 STEMI에서 남성과 여성 간의 차이가 없었지만, NSTEMI에서 남성에서 유의하게 높았다(96.9% vs. 95.8%, p=0.004). 결 론： 한국인 급성 심근경색증의 초기 치료에 있어서 여성이 남성 보다 보존적으로 치료받았고, 이는 여성 환자의 나이가 많았기 때문이었다. PCI 성공률은 남성에서 여성 환자보다 높았다. Background and Objectives：The first on-line registration of Korea Acute Myocardial Infarction patients (KAMIRs)has been carried out throughout the 41 primary percutaneous coronary intervention (PCI) centers that aresupported by the Korean Circulation Society (KCS), as reported in the memorandum of the 50th Anniversary ofthe KCS. Subjects and Methods：Between Nov 2005 and June 2006, 4905 patients were enrolled in KAMIR and4110 eligible patients (2855 males and 1255 females; mean age=64.3±13.5 years) were analyzed. The treatmentstrategy for acute myocardial infarction (AMI) was analyzed according to the gender differences in the area of acuteST segment elevation myocardial infarction (STEMI) and non-ST segment elevation myocardial infarction (NSTEMI).Results：For the initial selection of a treatment strategy for STEMI, primary PCI was more commonlyperformed in males than females (69.8% vs. 68.3%, respectively, p=0.008), but age was the most important predictorsafter multivariate adjustment. During the hospital stay, PCI regardless of its subtype was more commonly done inthe males than in the females with both STEMI and NSTEMI (STEMI: 89.1% vs. 84.9%, respectively, p=0.004;NSTEMI: 74.7% vs. 63.5%, respectively, p<0.001). The success rate of PCI in STEMI patients was not differentbetween the genders (95.0% vs. 93.6%, respectively, p=0.399), but that of NSTEMI was higher in the males thanthe females (96.9% vs. 95.8%, respectively, p=0.004). Conclusion：For the initial treatment of AMI in Korea, femalesare treated more conservatively than males, but age was the most important predictor for invasive treatment. Thesuccess rate of PCI was higher for the males than the females. (Korean Circulation J 2007;37:64-71) KCI Citation Count: 22